Optimization of non-uniform oscillating gradient spin echo sequences for selective microstructure-size imaging - Capiglioni, Milena Sofía (2023)
Diffusion-weighting imaging is a promising method for quantitative imaging of tissue microstructure features that may identify early stages of pathologies. Non-uniform oscillating gradient spin-echo (NOGSE) sequences are a novel technique to study diffusion spectra and quantitatively characterize tissue. The sequence contrasts the signal between two modulating gradient frequencies to filter the signal originating from molecules diffusion in specific restriction sizes. We determine the range of control parameters that maximizes NOGSE contrast for filtering the restriction sizes. We assess the restriction sizes that this sequence can filter with current technologies.